PENGARUH KONSELING SAAT ANTENATAL CARE TERHADAP PENGETAHUAN IBU HAMIL TENTANG TANDA BAHAYA KEHAMILAN DI KECAMATAN PALANGGA KABUPATEN GOWA - Zaenal (Stikes Graha Edukasi Makassar, 2021)
One of the causes of the still high maternal mortality rate is complications that occur in pregnant women which can be identified by recognizing the danger signs of pregnancy that appear. This study aims to determine the effect of counseling during antenatal care on pregnant women's knowledge about danger signs of pregnancy in Palangga District, Gowa Regency in 2015. This type of research was observational with a cross-sectional design which was conducted in September 2015. A sample of 72 people with details of 36 people in group I, namely primigravida pregnant women who received counseling and 36 people in group II, namely primigravida pregnant women who did not receive counseling in Palangga District. Collecting data using a questionnaire distributed to respondents. Data analysis was performed by t-test at a significance level of 95%. The results of the analysis obtained a p value = 0.400, which means there is no difference in knowledge between pregnant women who receive counseling and those who do not receive counseling so that there is no effect on the knowledge of pregnant women. Counseling that has been done so far has been ineffective. For this reason, it is suggested to midwives to carry out counseling according to standards and develop self-quality by having extensive knowledge so that they can provide the information needed